Unidade de ensino potencialmente significativa para estudo do sistema respiratório humano no Ensino Fundamental II - Cavalcanti, Juliano (2016)
One of the biggest challenges for teachers today is developing methodologies that incite the will to learn in students. Hence, a movement of teachers and researchers seeking to qualify the Sciences teaching and learning process is observed, especially in elementary school. In light of this need, added by the perception that methodologies used to teach this curricular component are having little effect as enablers in content appropriation, the present study seeks to develop, apply, and evaluate a didactic and methodological proposal based on the cognitive theory of Significant Learning by David Ausubel. More specifically, the work develops a Potentially Significant Teaching Unit (UEPS) for the topic of respiratory system in the final years of elementary school, so to analyze the relevance of the proposal regarding its feasibility as didactic strategy. The guiding questions of the study are: Is the UEPS a methodology that promotes dialogue and debate in the classroom? How do students behave facing didactic approaches that excel by their active participation in the construction of their own knowledge? Is the structure proposal in the form of an UEPS feasible for the content of respiratory systems in the final years of elementary school? Seeking to answer these questions, the study is characterized as qualitative and descriptive, relying data collection on a logbook produced after each meeting by a teacher-researcher. The application of the didactic proposal was given in an eighth-year class of a public elementary school in the city of Passo Fundo, RS, Brazil, at the second semester of 2015. The results of the study, revealed by the logbook, indicate the feasibility of the proposal, especially in terms of its potential for student engagement and questioning. The investigation, which is part of the line of research Theoretical and methodological basis for Sciences and Math teaching , presents a blog as educational product, wherein the didactic strategies used in the application of the proposal are described, videos are offered, and the meetings that took place during the UEPS application are reported.